Spectroscopic, Mechanical, and Thermal Characterization of Native and Modified Nigerian Coir Fibers. Issue 5 (2nd September 2016) - Akintayo, C. O.; Azeez, M. A.; Beuerman, Sabine; Akintayo, E. T.
ABSTRACT: Coir fibers native to Nigeria and their modified forms viz: acetylated coir, oxidized coir, and mercerated coir have been characterized by spectroscopic, thermal, mechanical, and microscopic techniques. The CP/MAS 13 C NMR spectra revealed that the modification of these fibers did not affect the cellulose type (C-1) and that the fibers are moderately crystalline. All the fibers can be said to be thermally stable until 200°C and based on the cumulative mass loss at 400°C modification of the coir fibers promoted an increase in thermal stability in the order mercerated coir > oxidized coir > acetylated coir > native coir. The mechanical and morphological properties of the native and modified Nigerian coir were also investigated using universal testing machine and scanning electron microscope, respectively, and the results are discussed.